The effects of small-sided soccer games on technical actions and skills: A systematic review - Clemente, Filipe Manuel (2020)
Purpose. This systematic review aims to describe evidence of the effects of different small-sided soccer games (SSGs) on technical actions and technical performance. The article systematically reviews and organizes the effects of the most common task conditions and characterizes the methodologies employed in previous studies. Methods. A systematic review of Web of Science, PubMed, and SPORTDiscus databases was conducted in accordance with preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The search returned 339 records. After screening against the set criteria, a total of 37 full articles were fully reviewed. Results. The main topics related to consequences of technical actions were (1) effects of different formats; (2) effects of different pitch sizes, relative area per player, pitch restrictions and configurations; (3) effects of different task conditions; (4) effects of age group, experience, and technical skill; and (5) effects of different training regimens or structured training programs. Briefly, it was concluded that smaller formats meaningfully increased the number of determinant technical actions performed when compared with medium and larger formats (5 vs. 5 to 11 vs. 11). Furthermore, smaller amounts of relative area per player meaningfully increased most technical actions made by players. The use of free play increased the number of technical actions taken, while imposing a 1-touch limitation raised the number of involvements but also the frequencies of errors and balls lost. Conclusions. This systematic review reveals that each of the above-mentioned topics has a meaningful impact on the frequencies of technical actions and success during SSGs.